Autonomic changes as reaction to experimental social stress in an inpatient psychosomatic cohort - Thurner, Carolin; Horing, Bjoern; Zipfel, Stephan; Stengel, Andreas; Mazurak, Nazar (Frontiers in Psychiatry, 2022)
Objectives: Patients with psychosomatic disorders suffer from social isolation that might further lead to destabilization and exacerbation of bodily symptoms via autonomic pathways. We aimed to investigate the influence of controlled social stress (model of social ostracism) on the autonomic nerve system (ANS) in an inpatient cohort with psychosomatic disorders. Methods: We examined heart rate variability (HRV), skin conductance (SC) and skin temperature (ST) as well as ECG-derived respiration rate (EDR) and subjective reports on stress during exposure to experimental social stress (cyberball game). Data were collected from 123 participants (f:m=88:35, 42.01±13.54 years) on admission and upon discharge from the university psychosomatic clinic. All data were recorded during baseline, inclusion and exclusion phases of the cyberball game as well as during the recovery phase. Results: We found significant changes between admission and discharge with a decline in parasympathetic-related HRV parameters (SDRR -3.20±1.30 ms, p=0.026; RMSSD: -3.77±1.28 ms, p=0.007) as well as a decrease in SC (-0.04±0.17 µS, p=0.019) and EDR (-0.01±0.01 Hz, p=0.007), suggesting a drop in sympathetic tonus, with no changes in ST (p=0.089) and subjective stress levels (p=0.322). HRV parameters decreased during the cyberball game (SDRR p=0.026; RMSSD p=0.002; lnHF p<0.001). In contrast, both SC (p<0.001) and EDR (p<0.001) increased during the game with SC being slightly lower during the exclusion phase. This can point toward a stimulation of sympathetic nervous system during game participation, which was concordant with the rise in subjective stress values (p<0.001). ST showed a continuous, unspecific rise over time (p<0.001). Conclusion: Our data demonstrate the decrease of ANS parameters during experimental social stress when data upon discharge were compared to those upon admission. These results are partially contradictory to previous studies that showed a rise in HRV in a psychiatric cohort over the course of (outpatient) treatment. Further research is required to help attributing these differences to effects of treatment or acute states relating to admission to or discharge from a psychosomatic department.